2015
DOI: 10.1371/journal.pone.0123067
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Umbilical and Cerebral Doppler in Fetal Growth Restriction: Comparison of Dichorionic Twins and Singletons

Abstract: ObjectiveTo compare the prognostic value of fetal Doppler in dichorionic twins and singletons by measuring the interval between diagnosis of an abnormal Doppler flow and birth in fetuses who are small for gestational age (SGA).DesignComparative retrospective study using a prospectively collected database.SettingA level 3 maternity unit in France.PopulationFetuses from singleton and dichorionic pregnancies who are SGA (vascular or unexplained), defined by an abdominal circumference (AC) measurement below the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
14
1
Order By: Relevance
“…Inconsistencies amongst clinicians and researchers with regards to the diagnostic criteria used for the definition of sFGR make the prevalence of this condition difficult to determine. Some studies define sFGR as one twin with estimated fetal weight (EFW) or abdominal circumference (AC) < 10 th centile, while others use EFW/AC discordance between the twins of > 20% or > 25%. While the incidence of sFGR is estimated to be 10–15% of twin pregnancies, this incidence is likely to vary according to whether the diagnostic criteria rely only on the EFW/AC of one twin or also incorporate intertwin discordance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistencies amongst clinicians and researchers with regards to the diagnostic criteria used for the definition of sFGR make the prevalence of this condition difficult to determine. Some studies define sFGR as one twin with estimated fetal weight (EFW) or abdominal circumference (AC) < 10 th centile, while others use EFW/AC discordance between the twins of > 20% or > 25%. While the incidence of sFGR is estimated to be 10–15% of twin pregnancies, this incidence is likely to vary according to whether the diagnostic criteria rely only on the EFW/AC of one twin or also incorporate intertwin discordance.…”
Section: Introductionmentioning
confidence: 99%
“…It seemed acceptable to use different diagnostic criteria for the same condition in DC and MC twin pregnancies, as the pathology leading to sFGR differs according to the type of twin pregnancy. DC twin pregnancies complicated by sFGR have conventionally been managed as FGR in singleton pregnancy, but recent evidence questions this approach. In MC twin pregnancy, sFGR is thought to result mainly from unequal placental share.…”
Section: Introductionmentioning
confidence: 99%
“…As the existing literature on sFGR in DC twin pregnancies is scarce, and they are managed in a similar fashion to singleton pregnancies, we have adopted an approach to extrapolate from singletons with FGR. Vanlieferinghen et al found that the time from the first abnormal umbilical artery Doppler finding to the time of delivery was significantly longer in growth restricted DC twins than in singletons (53 vs. 16 days), and that twins with sFGR were delivered later than singletons, with no difference in outcome [9]. This could be due to clinician bias, in order to delay delivery for the sake of the AGA twin, or could reflect a slower disease progression in twins compared to singletons.…”
Section: Interpretation Of Study Findings and Comparison With Existinmentioning
confidence: 99%
“…Recent evidence has suggested that the natural history of sFGR in DC twins may not be so similar to that of singletons. Vanlieferinghen et al have found that the interval from development of umbilical artery Doppler abnormalities to birth was significantly longer in growth restricted DC twins than in growth restricted singletons [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the question arises whether different mechanisms intervene in fetal growth and whether the results in this study (especially regarding abdominal circumference) are not as extreme as in our previous study population because this is counteracted more strongly. A recent study, conducted by Vanlieferinghen et al [25], observed that twins were less severely SGA than singletons and that the interval from development of umbilical artery Doppler abnormalities to birth was significantly longer in growth-restricted twins than in growth-restricted singletons [25]. In general, the pathophysiological mechanism of fetal growth restriction in twins may be related to failed placentation and pathological blood flow distribution.…”
Section: Discussionmentioning
confidence: 99%